First Report of a Novel Unbalanced Complex Variant Translocation t(3;9;22) with Ph Duplication and Evolving Triple Trisomy (8,12,21) in Newly Diagnosed Chronic Myeloid Leukemia without Blast Crisis: Resistance to Frontline Therapy - Abunaser, Suhaib Mohammad Ali; Sudha, Shruti Prem; Pais, Anurita (Indian Journal of Medical and Paediatric Oncology, 2025)
In chronic myeloid leukemia (CML), tyrosine kinase inhibitors (TKIs) targeting the BCR/ABL1 fusion gene have transformed CML into a manageable condition. While most cases involve the standard t(9;22) translocation, 5 to 10% exhibit variant translocations and/or additional chromosomal abnormalities (ACAs), often linked to disease progression. Hence, cytogenetic analysis is crucial for monitoring clonal evolution and guiding treatment.This report presents a unique case of chronic-phase CML with a three-way unbalanced variant translocation involving chromosomes 3, 9, and 22, alongside an interstitial deletion of the reciprocal ASS1/ABL1/BCR region. ACAs with Ph duplication and trisomy of chromosomes 8, 12, and 21 in the present case complicate the genomic landscape, with specific breakpoint involvement and additional abnormalities indicating a poorer outcome, highlighting the need for further investigation and tailored treatment strategies.Given the rarity and poor prognostic association of this finding, our study highlights the importance of identifying complex chromosomal variations to enable modified targeted therapy regimens as first-line treatment. This emphasizes the need for individualized prognostic assessment and continuous monitoring to optimize therapeutic outcomes.
Keywords: chronic myeloid leukemia; variant translocation; karyotype; fluorescence in situ hybridization; imatinib; ponatinib